Enhancing Student Participation through Gamification-Based Digital Learning Media: A Study of Structural Gamification - Ratna Rufaida; Aisyah, Nur; Rozi, Fathor; Lama, Alma Vorfi (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
This study investigates the implementation of digital gamification at MTs Nurul Jadid as a strategy to enhance student participation in learning. With the increasing integration of digital technology in education, gamification offers a promising approach to boost student motivation and engagement. Using a qualitative case study design, this study examines key gamification elements, including point systems, levels, and leaderboards, within teaching and learning activities. The findings reveal that gamification positively influences students' intrinsic motivation, leading to increased participation in discussions, questions, and interactions with teachers. This approach fosters a more interactive and enjoyable classroom environment, promoting intensive collaboration and social interaction among students, while improving teacher-student relationships. Consequently, learning extends beyond knowledge transfer to active peer collaboration and mutual support. The study contributes valuable insights toward developing gamification-based learning models suitable for Islamic boarding schools and other educational institutions, aiming to improve learning effectiveness in line with contemporary educational trends.